Promoting Energy Efficiency in Panpacific University, Philippines - Donna Padilla-Taguiba; Jesus Deogracias Principe; Marvin Sermonia Jr.; Marvin Calpito (Universitas Diponegoro, 2025)
Panpacific University, located in the northern part of the Philippines, has been active in promoting the United Nations’ Sustainable Development Goal No. 7, or the push towards affordable and clean energy, by promoting sustainable energy use through a variety of energy efficiency initiatives. These initiatives include: (a) the University’s commitment towards channelling renewable energy through the installation and use of photovoltaics, so that this array of solar panels may generate sufficient energy to become a major contributor in meeting the demand of the school’s energy consumption needs; (b) the replacement in the campus buildings of more conventional incandescent or fluorescent light bulbs with lower cost and longer-lasting LED lamps for both greater energy efficiency and lower energy use and maintenance costs; and (c) the setting up of various school guidelines and policies aimed at promoting personal and institutional responsible energy consumption and also at further raising awareness of the need to take a more sustainable approach towards resource use, as well as encouraging further study and discovery in this area. This current report serves to detail the implementation of these initiatives, and the results achieved to date. As the school goes through a restructuring process and installs a newly appointed Sustainability Officer tasked now to oversee these initiatives, a further discussion on the projected targets and potential future directions that these initiatives might take is also in order. It is hoped that this information might be of use for other Higher Educational Institutions in the locality or in the region towards their own energy efficiency efforts.